Clinical profile of patients with diabetes: a hospital based cross sectional study - Sabbani, Abhishek; Medidhi, Keerthana (International Journal of Advances in Medicine, 2021)
Background: Diabetes is a leading cause of morbidity and mortality. Early identification of complications and management of the same is important to prevent the morbidity and mortality. The objective of the study was to study the clinical profile of patients with diabetes. Methods: A hospital based cross sectional study was carried out among 25 diabetic individuals. Baseline demographic details, risk factors and complications were noted. Investigations like fasting blood sugar, lipid profile and blood pressure were carried out for all patients. Their treatment status was noted. Results: Majority (56%) belonged to age group of 40-59 years. Males were more (64%) than females (36%). Only 28% were normal weight. 52% admitted that they consumed alcohol. 72% were non-smokers and only 8% were tobacco chewers. Hypertension was the most common complication associated with diabetes in 64% of the cases. 4% each had coronary heart disease, stroke, and neuropathy. No one was found to have cataract. 12% had diabetic foot while 8% had kidney disease. Mean levels of total cholesterol was 164.76; mean level of triglyceride was 169.28; mean level of HDL was 45.08; mean level of LDL was 91.32; mean level of Fasting blood sugar was 186; mean Systolic blood pressure was 168.48 and mean Diastolic blood pressure was 114.4. Majority (76%) were on Oral hypoglycemic drugs only and only 4% were on insulin. 20% were on Oral hypoglycemic drugs + insulin. Conclusions: Males were affected more with diabetes. Hypertension was the most common complication. Significant number had developed serious complications and hence early screening for complications in all diabetes patients is required.